Two-level algorithms for Rannacher-Turek FEM - Georgiev, I.; Kraus, J.; Margenov, S. (Інститут програмних систем НАН України, 2006)
In this paper a multiplicative two-level preconditioning algorithm for second order elliptic boundary value problems is considered, where the discretization is done using Rannacher-Turek non-conforming rotated bilinear finite elements on quadrilaterals. An important point to make is that in this case the finite element spaces corresponding to two successive levels of mesh refinement are not nested in general. To handle this, a proper two-level basis is required to enable us to fit the general framework for the construction of two-level preconditioners originally introduced for conforming finite elements. The proposed variant of hierarchical two-level splitting is first defined in a rather general setting. Then, the involved parameters are studied and optimized. The major contribution of the paper is the derived uniform estimates of the constant in the strengthened CBS inequality which allow the efficient multilevel extension of the related two-level preconditioners.